A review of the use of natural pigments in multilayer and composite films for intelligent biodegradable food packaging - Yildirim-Yalcin, Meral; Kemerli-Kalbaran, Tansel; Ceyhan, Tugce; Mojtahedi, Esin; Olcay, Hatice Sena; Sahin, Selin; Falsafi, Seid Reza; Toker, Omer Said (ELSEVIER SCIENCE SA, 2026)
Composite and multilayered forms of biodegradable packaging are manufactured in order to improve the qualities of the films. This kind of packaging has gained attention as a consequence of the problem of plastic waste. Natural pigments alter the color of packaging films as a result of pH changes due to components released during food deterioration, thus providing information about the food's status and functioning as intelligent packaging. This review covers the recent studies on the use of natural pigments for the production of biodegradable composite and multilayer intelligent packaging. In addition, a coating-design perspective is adopted to examine how layer structure, pigment incorporation, and polymer-pigment interactions shape the functional performance of multilayer and composite films. The review emphasizes structure property relationships central to coating science by summarizing key characterization techniques including mechanical, barrier, optical, and thermal analyses and explaining how natural pigment incorporation modifies the performance of multilayer and composite films. The possibilities of using biodegradable films containing natural pigments as spoilage indicators in food packaging are also summarized. The selection of appropriate biopolymers and pigments is important for the production of a high-quality film that can act as an indicator at the desired pH. Overall, this review integrates advancements in intelligent biodegradable packaging with principles of organic coating technology, outlines current challenges associated with pigment stability and coating durability, and highlights future research directions for developing scalable, high-performance functional coatings.
Keywords: Composite films; Intelligent packaging; Multilayer films; Natural pigments; ANTHOCYANINS; ALCOHOL; BETACYANINS; FRESHNESS; GELATIN; CABBAGE; BLEND; L.; Chemistry; Materials Science